Pendulous lichen colonization in small gap openings can enable a resource continuum for reindeer - Rikkonen, Taru; Hallikainen, Ville; Turunen, Minna; Rautio, Pasi (Suomen metsätieteellinen seura, 2025)
In northern Finland, continuous cover forestry (CCF), has been introduced to better reconcile multiple land uses, including commercial forestry and reindeer husbandry. We studied how small gap cutting, a CCF method, can facilitate the colonization of pendulous lichens (Alectoria sp., Bryoria sp., and Usnea sp.), a bottle-neck resource for reindeer (Rangifer tarandus tarandus), into harvested areas. To assess the potential for balancing between forestry and reindeer husbandry, we investigated the colonization success of pendulous lichen on seedlings within the gaps created ten years before onset of our study in a pine-dominated boreal forest in central Finnish Lapland. The study included three gap sizes (diameters 20, 40, and 80 m) in xeric and sub-xeric sites, arranged in six randomized blocks, with 18 replicates per each gap size. Additionally, we examined the influence of gaps on the abundance of pendulous lichens in mature trees in the surrounding forest. Our results indicate that pendulous lichens colonized the smallest gaps (d = 20 m) efficiently, while colonization success declined as gap size increased. Colonization was strongly associated with seedling density, as a higher number of seedlings within gaps increased the probability of lichen colonized seedlings. The highest colonization rates occurred near gap edges, with lower colonization in the center. Furthermore, seedling height positively influenced colonization, and the presence of pendulous lichens on adjacent mature trees enhanced seedling colonization within gaps. However, we also observed that gap edges significantly reduced the amount of pendulous lichens on mature trees.
Keywords: continuous cover forestry; forestry; uneven-aged forestry; multiple use of forests; reindeer husbandry; land use conflicts; small gap cutting